Hepatitis E vaccination status, knowledge, attitude, and practice among university freshmen: a cross-sectional study in China - Bi, Niannian; Wang, Axin; Gong, Lei; Nie, Shuang; Sun, Yuanfang; Wei, Hongyuan; Ma, Wanwan; Hou, Sai; Wu, Jiabing; Xiao, Yongkang (Frontiers in Public Health, 2025)
BackgroundHepatitis E virus (HEV) is a major global public-health threat. University students are at high risk of HEV infection. This study aimed to assess the knowledge, attitude, and practice (KAP) levels regarding hepatitis E among university freshmen and their willingness to receive HEV vaccination.MethodsA cross-sectional study was conducted from September to December 2023 among 3,276 freshmen from six universities in Anhui Province, China. Data were collected using structured questionnaires. A stratified cluster random sampling method was used to select participants. Multivariate logistic regression was performed to identify factors associated with KAP levels. Data were analyzed with SPSS version 23.0.ResultsOf the 3,276 questionnaires distributed, 3,120 were valid, with a response rate of 95.2%. Only 9.0% of participants had received the HEV vaccine. The overall correct knowledge rate of HEV was 50.8%. A positive attitude was reported by 59.9% of students, and 60.9% demonstrated good practices related to HEV. Multivariate analysis showed that vaccinated students had significantly higher knowledge levels than non-vaccinated students (OR = 1.999, 95% CI: 1.536–2.602). Female students (OR = 1.193, 95% CI: 1.029–1.382) and those from Wuhu (OR = 1.571, 95% CI: 1.299–1.900) also had higher knowledge levels. Medical students were more likely to have a positive attitude than non-medical students (OR = 1.367, 95% CI: 1.161–1.610). Students from rural areas (OR = 1.336, 95% CI: 1.148–1.553) and Wuhu (OR = 1.317, 95% CI: 1.088–1.594) showed higher levels of positive attitude. Rural students also reported better health practices than urban students (OR = 1.288, 95% CI: 1.088–1.524). The result also showed both knowledge (r = 0.042, P = 0.020) and attitude (r = 0.049, P = 0.006) exhibited statistically significant but weak positive correlation with practice.ConclusionsOver half of the university freshmen demonstrated good KAP levels regarding HEV. However, the vaccination rate remained low. Therefore, determinants identified will guide health promotion and vaccine advocacy.